Research on the key perception points in the process of e-book selection. Issue 5 (1st December 2020) - Xing, Sisi; Peng, Aidong; Mao, Yihong
Abstract : Purpose: This paper aims to propose some suggestions for libraries and other digital reading service institutions to improve the utilization rate of e-books, based on the theoretical and empirical analysis of the perception behaviour characteristics of e-book selection under the allocation of limited cognitive resources. Design/methodology/approach: From the perspective of key perception points, this paper studies the key perception points of selecting e-books through the experimental method and explores the influence of subject factors (users' characteristics, users' needs) on users' e-book perception behaviour. Findings: College students have selective attention in the process of selecting e-books. They will choose some important contents of e-books, such as title, book introduction, author, catalogue, reader comments, others' recommendations, read leaderboard, to perceive and there is an obvious difference in perception intensity. Different personal traits and reading needs have a great influence on users' perception points. Libraries and other digital reading service institutions should provide promotion information based on key perception points of e-books, develop personalized e-book service and promotion and optimize the expression of key perception points of e-books. Originality/value: This paper presents a valuable study attempting to introduce cognitive resource theory into the field of digital reading service, which proves that users also have limited cognitive resource allocation in the process of selecting digital books.